Energy absorption of impact damper - Annamalai Gurunathan, Balamurugan (2009)
The front and rear of the vehicle should be protected in such a manner that low speed collisions will only damage the vehicle slightly, or not at all. Kinetic energy due to the low speed collision could be as high as 1000 J. If this impact energy is not dissipated properly, it could damage the bumper and other components attached to it. In this project, circular tube was investigated to absorb the impact energy during low speed collision at 4 km/h. The thickness and length that gives hoop stress lower than yield strength of the material is selected. . Both analytical and numerical methods were used to find suitable thickness and length of the tube. Solid assembly model of the bumper, front cross member and circular tubes were developed. The bumper is simulated with impact force of 1333 N based on ECE/324 Regulation No.42. Both linear and non-linear simulation was carried out. Results show that circular tube exhibit good energy absorption behaviour.